1977
DOI: 10.1017/s0043174500033373
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses in Sorghum and Wheat Induced by Glyphosate

Abstract: Foliar application of 2.8 μg/plant of glyphosate [N-(phosphonomethyl)glycine] to greenhouse grown sorghum [Sorghum bicolor (L.) Moench ‘Tophand’] seedlings resulted in increased fresh weight. As glyphosate levels were increased to 11.2 μg/plant, diameter of the basal growth zone increased while fresh weight decreased. In growth chamber studies with sorghum and wheat [Triticum aestivum (L.) ‘Era’] seedlings, glyphosate caused the greatest reduction in fresh weight at the optimum growth temperatures for both spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…Zollinger et al [23] and Darwent, Kirkland, Baig and Lefkovitch [14] also reported that an application of glyphosate prior to the hard dough stage or physiological maturity caused decreases in kernel weight and kernel size. Similar observations, where harvest aids caused negative effects on grain quality, were found in other crops such as dry bean [24], sorghum seed [25], soybean [26], peas [27] and rice [28]. However, contrary to the findings of the current study, He et al [29], who studied the impact of the harvest aids, such as diquat, paraquat and ethephan on rice quality, reported that pre-harvest application of these herbicides did not affect the TKW of rice.…”
Section: Effects Of Glyphosate On Kernel Milling and Flour Qualitysupporting
confidence: 76%
“…Zollinger et al [23] and Darwent, Kirkland, Baig and Lefkovitch [14] also reported that an application of glyphosate prior to the hard dough stage or physiological maturity caused decreases in kernel weight and kernel size. Similar observations, where harvest aids caused negative effects on grain quality, were found in other crops such as dry bean [24], sorghum seed [25], soybean [26], peas [27] and rice [28]. However, contrary to the findings of the current study, He et al [29], who studied the impact of the harvest aids, such as diquat, paraquat and ethephan on rice quality, reported that pre-harvest application of these herbicides did not affect the TKW of rice.…”
Section: Effects Of Glyphosate On Kernel Milling and Flour Qualitysupporting
confidence: 76%
“…Growth inhibition was measured by stem counts (Table 1). When new shoots did appear midway through the growing season, shoot growth and branching from buds were observed, a characteristic of sublethal rates of glyphosate observed on other species (5,7,18,19). These observations indicate that glyphosate may have the ability to interfere with correlative inhibition, which is dormancy enforced by the main shoot, and facilitate prolific shoot bud growth from previously inhibited buds on leafy spurge plants.…”
Section: Translocation Experimentsmentioning
confidence: 74%
“…Glyphosate at sublethal concentrations causes tillering, axillary bud, and root bud growth in other species (5,7,18,19). These results indicate that glyphosate can temporarily overcome apical dominance either directly or indirectly and cause uncharacteristic stem and shoot growth.…”
Section: Introductionmentioning
confidence: 84%
“…further demonstrated that main shoot apical dominance limited imazametbabenz translocation to lateral shoots, rendering tillers less susceptible to growth inhibition by the herbicide. The release of apical dominance has also been demonstrated with glyphosate on Cvnodon dactvlon (Fernandez and Bayer 1977), wheat (Triticum aestivum^ and sorghum (Baur et al 1977). Shieh et al (1993) reported that the sink activity of various buds along old rhizomes of quackgrass increased, thus competing strongly with other nearby buds, which consequently received little assimilates and glyphosate.…”
Section: Introductionmentioning
confidence: 88%
“…Sublethal doses of glyphosate (iV^hosphonomethyl)glycine) applied to the foliage of quackgrass (Agropyron repens^ stopped the growth of shoots and caused prolific tillering . Under normal growth conditions, basal buds in sorghum (Sorghum bicolor^ do not develop; however, application of glyphosate stimulated basal bud development (Baur et al 1977). (Setaria faberi^ .…”
Section: Introductionmentioning
confidence: 99%